Beberapa Masalah Dalam Penyelesaian Hak Guna Usaha Atas Tanah Antara PT. Era Sakti Wiraforestama Dengan Masyarakat Adat Kecamatan Maro Sebo Kabupaten Muaro Jambi - Abdul Hariss (Jurnal LEX SPECIALIS, 2011)
The agreement concluded between the PT. Era Sakti Wiraforestama with Maro Sebo is indigenous land use agreement for business purposes, as outlined in the letter of agreement. In the agreement, held, determined the rights and obligations of each party, generally the right of the PT. Era Sakti Wiraforestama able to use land owned by indigenous peoples for the business activities of plantation until the specified time period with the obligation to pay the price of plantation management is carried out and return the land to indigenous people at the time of expiry of the agreement. While indigenous rights as the owner of land in addition to the plantation also get back their land after the expiration of the agreement. With the changes in the implementation of the agreement without being noticed by the citizens of indigenous Maro Sebo, grow a variety of issues such as: Claiming some of the land of indigenous people has become the property of PT. Era Sakti Wiraforestama who previously had no land rights in the region; Revenue results by the citizens of indigenous landowners are no longer in accordance with the treaty agreed upon in advance; and The absence of submission of return of land lease rights to the indigenous peoples while the term of the agreement has expired. The existence of the above problems, there arose a dispute between PT. Era Sakti Wiraforestama with the community residents customary right to cultivate the land owner district Maro Sebo. Disputes are not allowed to taper which ultimately could harm one or both sides that were previously bound by the agreement the use of land for plantation, but made various efforts for the settlement of disputes. Key Note : Rights For Completion Of The Land